2001
DOI: 10.1103/physrevlett.87.185002
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Interpretation of Alfvén Cascades in Tokamaks with NonmonotonicqProfiles

Abstract: Alfvén spectra in a reversed-shear tokamak plasma with a population of energetic ions exhibit a quasiperiodic pattern of primarily upward frequency sweeping (Alfvén cascade). Presented here is an explanation for such asymmetric sweeping behavior which involves finding a new energetic particle mode localized around the point of zero magnetic shear.The presence of energetic particles in a plasma can alter its behavior from that predicted by conventional magnetohydrodynamics (MHD) theory in two ways. First these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
275
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(290 citation statements)
references
References 16 publications
13
275
0
Order By: Relevance
“…the determination of plasma parameters via the frequency evolution of these modes has to be examined. Recently, reversed shear Alfvén eigenmodes (RSAE) [5] attracted a lot of attention. Due to advances in both the experimental measurements and the code simulation capabilities, refined information about their 2d mode structures [6,7] and transition to TAEs [8] could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…the determination of plasma parameters via the frequency evolution of these modes has to be examined. Recently, reversed shear Alfvén eigenmodes (RSAE) [5] attracted a lot of attention. Due to advances in both the experimental measurements and the code simulation capabilities, refined information about their 2d mode structures [6,7] and transition to TAEs [8] could be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…12 and 13) and similar to the EPM which is predicted for ICRF heated plasma with reversed magnetic shear. 14,15 However, it was shown numerically that the reversed-shear-induced Alfvén eigenmode, 16 which has properties similar to the global Alfvén eigenmode, 17 can exist in reversed shear plasmas. It was demonstrated that MHD theory can explain frequency chirping behavior of so-called Alfvén cascades observed in reversed shear plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…In RS tokamak plasmas, characteristic energetic-iondriven modes called RSAEs or Alfvén cascade modes are observed [23][24][25][26][27][28][29][30][31]. Moreover, a GAM having an n = 0 mode structure is sometimes excited by energetic ions [32,33].…”
Section: Aes In Reversed Magnetic Shear Plasmasmentioning
confidence: 99%